CONTRIBUTION DE LA COOPERATION MULTILATERALE RDC-PNUD AUX EFFORTS DU DEVELOPPEMENT DU GOUVERNEMENT CONGOLAIS - Dieudonné, MAGAY MISSA; Aimée, BUAGUO UIPAKUODE; Castro, MBULA ABDI (IJRDO - Journal of Social Science and Humanities Research, 2021)
This research focuses on the DRC-UNDP multilateral contribution to the development efforts of the Congolese government. This work attempts to offer a dynamic partnership, shedding light on the contribution of multilateral between the DRC and the UNDP.Indeed, the behavior of macroeconomic and gorvenance indicators is gradually improving, but the prevalence of poverty, the infrastructure deficit, corruption and poor gouvernance, innovations and many other natural disasters are still matters of concern.